2022
DOI: 10.3390/su14148368
|View full text |Cite
|
Sign up to set email alerts
|

Carving out a Niche in the Sustainability Confluence for Environmental Education Centers in Cyprus and Greece

Abstract: Given the environmental issues that today’s societies confront, such as climate change, waste management, ecosystem deterioration, etc., environmental education is becoming increasingly important. Adoption of environmental education as an integral part of the educational system is required for the Environmental Education Center (EEC) to be able to provide knowledge, skills, and values so that society can become active and environmentally responsible through awareness-raising. According to the scholarly publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 64 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…In particular, research has shown that students perceive energy communities as strategically important for decarbonization; further training could reinforce this belief 25 . Educational aspects are essential to foster the development of a mindful attitude toward sustainable issues 54 , 55 . In the literature, energy communities are mainly conceptualized as places, rather than participatory processes.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, research has shown that students perceive energy communities as strategically important for decarbonization; further training could reinforce this belief 25 . Educational aspects are essential to foster the development of a mindful attitude toward sustainable issues 54 , 55 . In the literature, energy communities are mainly conceptualized as places, rather than participatory processes.…”
Section: Resultsmentioning
confidence: 99%
“…Raising awareness about the benefits of the circular economy and educating individuals and businesses about circular practices can be powerful motivators. Campaigns can highlight the environmental, economic and social advantages of circularity, inspiring behaviour change and encouraging adoption of circular practices ( Eliades et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…bins), lack of knowledge on waste collection and CDW implications (i.e. education, training of staff) but also lack of national and regional legislation on CDW disposal ( Eliades et al, 2022 ; Loizia et al, 2021 ; Zorpas et al, 2021 ). Through the designing of new strategies, site culture is a very important pillar for the adequate transition towards circularity.…”
Section: Resultsmentioning
confidence: 99%